2018
DOI: 10.1186/s12974-018-1222-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular identification of the immune response in peripheral ganglia following nerve injury

Abstract: BackgroundNeuroinflammation accompanies neural trauma and most neurological diseases. Axotomy in the peripheral nervous system (PNS) leads to dramatic changes in the injured neuron: the cell body expresses a distinct set of genes known as regeneration-associated genes, the distal axonal segment degenerates and its debris is cleared, and the axons in the proximal segment form growth cones and extend neurites. These processes are orchestrated in part by immune and other non-neuronal cells. Macrophages in ganglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 83 publications
9
45
2
Order By: Relevance
“…Csf1). Indeed, neuron-macrophage interactions promote the conditioning injury effect and axon regeneration of DRG neurons (Kwon et al, 2015;Lindborg et al, 2018;Niemi et al, 2013). Therefore, DLK may activate the pro-regenerative program in part via a non-cellautonomous mechanism that promotes gliosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Csf1). Indeed, neuron-macrophage interactions promote the conditioning injury effect and axon regeneration of DRG neurons (Kwon et al, 2015;Lindborg et al, 2018;Niemi et al, 2013). Therefore, DLK may activate the pro-regenerative program in part via a non-cellautonomous mechanism that promotes gliosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…4d). Several studies suggested a predominant anti-inflammatory macrophage phenotype in the DRG following sciatic nerve injury 23,24,71,72 , but these studies were limited by immunofluorescence approaches.…”
Section: Macrophages Enhanced Proliferation In Response To Peripheralmentioning
confidence: 99%
“…Using multiparameter FACS analysis, we observed an infiltration of various immune cells in general in wild-type mice at the site of injury of the sciatic nerve (SN) 7 days after SNI surgery ( Figure 2 A). The infiltration of immune cells to the DRGs and the spinal cord after nerve injury has been demonstrated before and usually peaks around days 5–10 after surgery [ 46 , 47 , 48 , 49 ]. Based on these observations, we considered 7 days after surgery an appropriate timepoint to investigate immune cell infiltration into nervous tissue.…”
Section: Resultsmentioning
confidence: 99%